Determinan Kualitas Laporan Keuangan Pada Perusahaan Agriculture BEI - Dody Salden Chandra; edisah putra nainggolan (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
The purpose of this study was to determine the determinant factors that affect the quality of financial reports in the Agriculture sector listed on the Indonesia Stock Exchange (IDX). This study uses an associative approach with a population of 9 Agriculture sector companies, while the sample that meets the criteria for sampling for this study is 6 Agriculture sector companies listed on the Indonesia Stock Exchange. Data collection techniques in this study is to use documentation techniques. The data analysis technique in this study uses Multiple Regression Analysis. The results of this study prove that Leverage partially affects the Quality of Financial Statements, Liquidity partially affects the Quality of Financial Statements, Company Size partially affects the Quality of Financial Statements. And simultaneously states that Liquidity, Leverage, and Company Size affect the Quality of Financial Statements in Agriculture sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period